2022
DOI: 10.1093/psyrad/kkac004
|View full text |Cite
|
Sign up to set email alerts
|

transcranial Direct Current Stimulation (tDCS) for the treatment and investigation of Phantom Limb Pain (PLP)

Abstract: Phantom limb pain (PLP) is a complex medical condition that is often difficult to treat, and thus can become detrimental to patients’ quality of life. No standardized clinical treatments exist and there is no conclusive understanding of the underlying mechanisms causing it. Noninvasive brain stimulation (NIBS) has been used to find correlations between changes in brain activity and various brain conditions, including neurological disease, mental illnesses, and brain disorders. Studies have also shown that NIBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…In addition, many studies run the models on the example head included with ROAST or an individual sample from the investigators. These work cover various clinical applications including: attention-deficit hyperactivity disorder [ 61 , 62 ], aging [ 63 ], associative memory [ 64 , 65 ], attention [ 66 – 68 ], body awareness [ 69 ], cognitive control and function [ 70 ]; Fusco et al [ 125 ]; [ 71 , 72 ], connectivity [ 73 ], decision making [ 74 77 ]; Schulreich and Schwabe [ 126 ], declarative learning [ 78 ], depressive disorder [ 79 ], electroencephalography (EEG) research [ 80 83 ], imitation [ 84 ], memory retrieval [ 85 87 ], mind wandering [ 88 , 89 ], motor learning [ 90 95 ], motor skills [ 96 98 ], neurorehabilitation [ 60 ], neurovascular coupling [ 99 ], obsessive-compulsive disorder [ 100 ], phantom limb pain [ 101 ], post-anoxic leukoencephalopathy [ 102 ], reading speed [ 103 ], schizophrenia [ 104 ], social anxiety disorder [ 105 ], stroke [ 106 ], visual perception [ 107 , 108 ], and working memory [ 109 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, many studies run the models on the example head included with ROAST or an individual sample from the investigators. These work cover various clinical applications including: attention-deficit hyperactivity disorder [ 61 , 62 ], aging [ 63 ], associative memory [ 64 , 65 ], attention [ 66 – 68 ], body awareness [ 69 ], cognitive control and function [ 70 ]; Fusco et al [ 125 ]; [ 71 , 72 ], connectivity [ 73 ], decision making [ 74 77 ]; Schulreich and Schwabe [ 126 ], declarative learning [ 78 ], depressive disorder [ 79 ], electroencephalography (EEG) research [ 80 83 ], imitation [ 84 ], memory retrieval [ 85 87 ], mind wandering [ 88 , 89 ], motor learning [ 90 95 ], motor skills [ 96 98 ], neurorehabilitation [ 60 ], neurovascular coupling [ 99 ], obsessive-compulsive disorder [ 100 ], phantom limb pain [ 101 ], post-anoxic leukoencephalopathy [ 102 ], reading speed [ 103 ], schizophrenia [ 104 ], social anxiety disorder [ 105 ], stroke [ 106 ], visual perception [ 107 , 108 ], and working memory [ 109 115 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the past 20 years have seen much research on the effects of tDCS on both the brain and pain (7), the accumulated results of the early investigations highlighted only modest and short-term analgesic effects. More recently, researchers hypothesized that combining tDCS with another neuromodulatory treatment could enhance analgesic effects (7)(8)(9)(10)(11).…”
Section: Combining Tdcs With Other Non-pharmacological Neuromodulator...mentioning
confidence: 99%
“…A meta-analysis by Bai et al, concluded that tDCS is effective for stroke recovery of patients with motor dysfunction 27 . Furthermore tDCS has been used in the rehabilitation of several additional neurological disorders such as depression, anxiety, and schizophrenia 24 , 25 , 28 , as well as for the relief of PLP 29 .…”
Section: Introductionmentioning
confidence: 99%
“…We undertake research in the field of prosthetic limbs 5 , 6 , rehabilitation of PLP 14 , 29 , and stroke 32 which would all benefit from validating the efficacy of tDCS to improve MPR. Here, we evaluated the hypothesis that tDCS improves MPR in the non-dominant hand of able-bodied individuals in a cross-over, sham-controlled study.…”
Section: Introductionmentioning
confidence: 99%